Penerimaan Sakramen Baptis bagi Bayi dari Pasutri yang Mengalami Halangan Perkawinan Katolik - Lumen Christian, Stefanus (Felicitas, 2023)
Sacraments are signs and means of God's saving presence. The sacrament of Baptism is one of them so that baptism also shows the salvation that comes from God. Everyone can receive the Sacramentof Baptism. This is because the Sacrament of Baptism makes everyone, who receives it, a member of the Church. In fact, they also receive an eternal seal that makes them commissioned to proclaim God's salvation. Receiving the Sacrament of Baptism means being born again to become children of God. In the Baptism ceremony, water is the main material because water is a means of cleansing. In fact, water has a great role for human life. The word "βαπτω" (bapto - Greek) or "βαπτιζω" (baptiso - Greek) means "to submerge", "to immerse", "to lower into water", "to plunge into water." The sacrament of Baptism has been the subject of discussion for the Church fathers who gave explanations about Baptism and the rituals performed. When looking at the history of Baptism and who can receive the Sacrament of Baptism, children from newborn to toddler age can receive it even if the parents have an impediment to Catholic marriage. The assistance provided by godparents can direct children to live like Jesus Christ, who is the source of salvation for mankind. The Sacrament of Baptism is the entrance to receive the other sacraments. By receiving the Sacrament of Baptism, a person who receives it has been reborn as a child of God and joined the communion of the Church. Thus, children who have received the Sacrament of Baptism can one day be a guarantee for the salvation of humanity who long for the saving presence of God, including couples (parents of children) who experience obstacles to Catholic marriage who long for the sacraments of salvation, through their example as true believers.